A missense variant in CREBRF is associated with taller stature in Samoans. Issue 6 (19th March 2020) - Carlson, Jenna C.; Rosenthal, Samantha L.; Russell, Emily M.; Hawley, Nicola L.; Sun, Guangyun; Cheng, Hong; Naseri, Take; Reupena, Muagututi'a S.; Tuitele, John; Deka, Ranjan; McGarvey, Stephen T.; Weeks, Daniel E.; et al.
Abstract: Objectives: Studies have demonstrated that rs373863828, a missense variant in CREBRF, is associated with a number of anthropometric traits including body mass index (BMI), obesity, percent body fat, hip circumference, and abdominal circumference. Given the biological relationship between height and adiposity, we hypothesized that the effect of this variant on BMI might be due in part to an association of this variant with height. Methods: We tested the hypothesis that minor allele of rs373863828 is associated with height in a Samoan population in two adult cohorts and in a separate cohort of children (age 5‐18 years old) using linear mixed modeling. Results: We found evidence of a strong relationship between rs373863828 and greater mean height in Samoan adults (0.77 cm greater average height for each copy of the minor allele) with the same direction of effect in Samoan children. Conclusions: These results suggest that the missense variant rs373863828 in CREBRF, first identified through an association with larger BMI, may be related to an underlying biological mechanism affecting overall body size including stature.